OP15 Targeted biopsy in suspected primary liver cancer – a single centre experience from Liverpool, UK. (20th September 2022) - Wood, Callum; Cross, Tim; Elshaarawy, Omar; Matthews, Charmaine; Avades, Tamar
Abstract : Background and Aims: The commonest primary liver cancers (PLC) include hepatocellular carcinoma (HCC – 75% of cases) and cholangiocarcinoma (CCa 6% of cases). Where uncertainty remains, e.g. in the absence background cirrhosis, a targeted biopsy can be performed to confirm the diagnosis. We describe a single centre experience in the use of liver biopsy for suspected primary liver cancer (PLC). Method: We describe an experience from a single centre in the UK. A database of patients referred to the liver cancer clinic is maintained and contained 935 patients from 2005 to 2021. Patients who had undergone biopsy were identified and their demographics and clinical data were compared to imaging and pathology results. Results: Fifty patients had undergone targeted liver biopsy. The median age was 70. The majority (n=37, 74%) were male. Exactly half (n=25) had cirrhotic liver disease, a further 3 (10.5%) had chronic liver disease without advanced fibrosis; 22 patients (44%) had no evidence of prior liver disease. The most common underlying aetiologies were hepatitis C (32.5%) and NAFLD (25%). The median diameter of all suspected PLCs was 50 mm, with a range between 10 and 154 mm. The modal diagnosis at biopsy was HCC (n=27, 48%), and where radiology was positively diagnostic, histology confirmed HCC in all cases. Other diagnoses included CCa (n=12, 25%); two mixed PLC; two lymphomas; two neuroendocrine tumours; two distal metastases; one gallbladder cancer; one hepatoma and one vascular malformation. In three patients no evidence of malignant tissue was identified in the biopsy sample. In two cases tissue was obtained at the point of microwave ablation therapy and one had previously undergone TACE. There was no evidence of significant complications such as major haemorrhage in any patient undergoing biopsy. Conclusion: Liver biopsy is a safe, valid and possibly under-utilized in the diagnosis and management of PLC.